Contrast Enhancement in Light Microscopy. Issue 1 (1st January 2013) - Ernst Keller, H.; Watkins, Simon
Abstract: The optical microscope is a fundamental component of an image cytometry system. This unit covers the basic concepts of light microscopy, including Köhler illumination, resolution, contrast, and numerical aperture, and reviews the many types of instruments and techniques for contrast enhancement. Curr. Protoc. Cytom . 63:2.1.1‐2.1.9. © 2013 by John Wiley & Sons, Inc.